Радіовиявлення та локалізація радіоакустичних закладних пристроїв - Школьник, В. А. (ХНУРЕ, 2024)
The article deals with the hardware and software complexes of detection and localization of radio-acoustic embedded devices, technical types of these complexes and their features.
Keywords: радіоакустичний закладний пристрій; радіовиявлення закладних пристроїв